OQÍWSHÍLARDÍ RUWXÍY ÁDEP-IKRAMLÍLÍQQA TÁRBIYALAW – INSANÍY PAZÍYLETKE BAǴDARLAW - Íqlasova, M. (SCIENCE and SOCIETY, 2022)
The article deals with the actual issues in teaching the valuable orientation of students, the fotmation of the human cognition, devolopment of moral gualities of students at shool and other educational establishments.